Spinning at the edges : a novel - Poliner, Elizabeth (Harper, 2026)
Ruth Pearl has lived in the small New England town of Wells, Connecticut on the shore of Lake Topaqua for much of her adult life. Decades back, she and her parents fled German-occupied Amsterdam after the murder of her beloved older sister Sophia. Her view of Lake Topaqua, in the wake of such loss, has long been a deep comfort to Ruth. But in the winter of 2000, Ruth's neighbor builds an addition to his home that blocks Ruth's lake view, disrupting her peace and sense of control. She seeks a legal resolution and finds none. Her helplessness sparks fear that her past is happening again. Ruth heads out one day to skate on the lake only to spot a boy, in the distance, falling through the ice. County judge Arthur Cantrell also witnesses the fall, and together Ruth and the judge save sixteen-year-old Ian Lima's life. The act is, for all of them, redemptive. Over the days to come Ruth and Arthur help to heal Ian, both physically and mentally, and all three find unexpected solace. Ruth even feels able, at long last, to share the story of her life during the Holocaust with her adult daughter.